PREFACE: THE 2021 EDITION OF THE XXIVTH ISPRS CONGRESS - C. Mallet; F. Lafarge; M. Poreba; T. Wu; G. Bahl; M. Yu; A. Garioud; Y. Chen; S. Jiang; M. Y. Yang; N. Paparoditis (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2021)
We report key elements and figures related to the proceedings of the 2021 edition of the XXIVth ISPRS Congress. Similarly to 2020, the COVID-19 pandemic caused global travel challenges and restrictions for the first half of 2021. Consequently, the physical Congress re-scheduled from June 2020 to July 2021 was again postponed to June 2022, still in Nice (France). Papers were already submitted and the ISPRS Council decided to carry out the review process and the publication of the proceedings of the papers submitted under the label “2021 Edition”. The authors of published papers had the opportunity to present their work during a Digital Event, this year scheduled the same week as the planned Congress (5–9 July 2021).